Development of a Validated HPLC-UV Method for the Determination of Panthenol, Hesperidin, Rutin, and Allantoin in Pharmaceutical Gel-Permeability Study - Sofia Almpani; Pavlina-Ioanna Agiannitou; Paraskevi Kyriaki Monou; Georgios Kamaris; Catherine K. Markopoulou (Separations)
A pressure ulcer is the necrosis of the skin and tissues due to prolonged pressure. Its prevention and treatment are of great importance not only for the health but also for the patient’s quality of life and are considered the highest priority. In the present study, a reliable analytical method is developed for the quantitative determination of panthenol, hesperidin, rutin, and allantoin by HPLC and UV detectors. The substances were formulated into a pharmaceutical gel, with healing and regenerative properties recommended for first- and second-degree bedsores. Their separation was achieved with a ZIC-Hilic column (150 × 4.6 mm), 5 μm, and a gradient elution system (Solvent A: CH3CN-H2O, 90:10 v/v/v and Solvent B: CH3CN-H2O, 10:90 v/v). The method was evaluated based on the required specifications (%RSD < 2, % Recovery > 96.7%) and was applied for the quantitative extraction of the active substances in the gel. The purification of the samples was carried out using experimental design and Cross-D-Optimal methodology (%RSD < 2.2, % Recovery > 96.9%). Subsequently, the gel was studied in terms of the transdermal permeation of the active pharmaceutical ingredients (APIs) through vertical Franz cells and their behavior (Papp values) was compared with a similar aqueous suspension product (reference formulation). The samples were reconstituted by lyophilization and extraction with methanol. According to the results, the drugs exhibit satisfactory penetration, ensuring the healing of problems that may occur in the skin and dermis.